How to Stimulate Myocardial Regeneration in Adult Mammalian Heart: Existing Views and New Approaches. (4th March 2020) - Belostotskaya, Galina; Hendrikx, Marc; Galagudza, Michael; Suchkov, Sergey
Abstract : Stem cell-based therapy has been considered as a promising option in the treatment of ischemic heart disease. Although stem cell administration resulted in the temporary improvement of myocardial contractility in the majority of studies, the formation of new cardiomyocytes within the injured myocardium has not been conclusively demonstrated. Consequently, the focus of research in the field has since shifted to stem cell-derived paracrine factors, including cytokines, growth factors, mRNA, and miRNA. Notably, both mRNA and miRNA can enter into the extracellular space either in soluble form or packed into membrane vesicles. Stem cell-derived paracrine factors have been shown to suppress inflammation and apoptosis, stimulate angiogenesis, and amplify the proliferation and differentiation of resident cardiac stem cells (CSCs). Such features have led to exosomes being considered as potential drug candidates affording myocardial regeneration. The search for chemical signals capable of stimulating cardiomyogenesis is ongoing despite continuous debates regarding the ability of mature cardiomyocytes to divide or dedifferentiate, transdifferentiation of other cells into cardiomyocytes, and the ability of CSCs to differentiate into cardiomyocytes. Future research is aimed at identifying novel cell candidates capable of differentiating into cardiomyocytes. The observation that CSCs can undergo intracellular development with the formation of "cell-in-cell structure" and subsequent release of transitory amplifying cells with the capacity to differentiate into cardiomyocytes may provide clues for stimulating regenerative cardiomyogenesis.